A Desintegrina e Metaloproteinase 10 (ADAM10) como biomarcadora para a doença de Alzheimer: uma revisão sistemática - Almeida, Maria Patrícia Oliveira Monteiro e Pereira de (2022)
Introduction: Studies have shown that Disintegrin and Metalloproteinase 10 (ADAM10) is the main α-secretase in the non-amyloidogenic cleavage of amyloid precursor protein (APP). ADAM10 prevents the production of β-amyloid peptide, one of the pathological features of Alzheimer's disease (AD). Objective: The objective of this work was to investigate ADAM10 present in cerebrospinal fluid (CSF), platelets and plasma/serum as a potential biomarker for AD. Methods: A systematic review was carried out in the Online System of Search and Analysis of Medical Literature databases (MEDLINE/PubMed), in the Database of bibliographic and citation information (Web of Science), in the Excerpta Medica Database (Embase) and in the bibliographic database for abstracts and citations of articles from academic journals (Scopus), as well as the manual search for citations, using the Boolean terms and operators: “Alzheimer” AND “ADAM10” AND “biomarker”. Inclusion criteria were original studies on ADAM10 in blood or CSF of patients with AD. Risk of bias was assessed using the Quality Assessment Tool for Observational Cohort and Cross-sectional Studies. The review protocol was registered in the PROSPERO database (CRD42021274239). Results: Of the 97 studies retrieved, 17 were included. There is strong evidence for lower levels of ADAM10 in platelets from people with AD compared to cognitively healthy participants. On the other hand, in plasma, higher levels of ADAM10 were found. Regarding CSF, controversial results were found with lower and higher levels of ADAM10 in people with AD compared to healthy elderly people. Conclusion: Evidence shows that ADAM10 levels are altered in platelets, plasma, serum and CSF of people with AD. The alteration was evident in all stages of the disease and, therefore, the protein may represent a complementary biomarker for AD. However, further studies should be carried out to establish cut-off values for ADAM10 levels to discriminate participants with AD from elderly people without cognitive impairment.